Macrofungi diversity in Lawu Mountain Forests and their potential uses as medicinal mushroom for inducing immunity against Covid-19. Issue 1 (November 2021) - Rahayu, S; Wardana, A F F; Nurjanto, H H; Anggara, G; Mahayani, N P D
Abstract: Macrofungi is one of bio-medicinal sources containing various bioactive compounds, such as β-glucans, which are scientifically proven as immunity booster against coronavirus, including Covid-19. Lawu Mountain Forest has been reported as one of the macro fungi-rich ecosystems in Java. Due to its unique geography, each side of the mountain has a different climate with the southern slope is typically more suitable for various species of mushroom to grow. The aims of this study were to assess fungal diversity in the southern slope of Lawu Mountain Forest, and to ascertain their potential uses for medicinal purpose, particularly for boosting immunity against Covid-19. Cruise method was used to identify macroscopic fungi collected along the hiking trail of Lawu Mountain Forest at the elevation ranges of 1800- 3100 m asl. Their morphological characteristics, including color, diameter, veil surface, lamella (ring and pore, type of lamella, and volva), stem shape, length and diameter, were observed. The study found 46 species from 15 families of macrofungi. Seven species potentially containing bioactive compounds as immunomodulator for boosting immunity were Auricularia auricula, Cerrena unicolor, Lentinus edodes, Pleuretus ostreatus, Stereum hirsutum, Schizophyllum commune, Trametes versicolor .